One Time And Seasonal Irrigation Norms Of Sorghum In Saline Soil Conditions - Ch.V.Toshpulatov; B.B.Tukhtashev (Zien Journals, 2025)
Non-compliance with sorghum irrigation norms remains an urgent issue for its cultivation in conditions of medium salinity soils. In order to obtain green mass in sorghum in medium saline gray-meadow soils of Syrdarya region, it is desirable to water 4 times at the rate of 540-770 m3 /ha in each irrigation, keeping 70- 80-70% compared to LFMC before irrigation the plant during the growing season is appropriate. When irrigating sorghum in this manner, 462-504 m3 /ha of water is saved from each hectare of sorghum field. This is an important factor in saving water, and is the highest measure to protect against secondary salinity in the conditions of saline soils
Keywords: conditions; important; irrigation; compared